TRANSTERIFICATION OF SOYBEAN OIL USING KI/ MESOPOROUS SILICA AS A CATALYST - Francio, Matheus; Silva, Michel Brasil (Anuário Pesquisa e Extensão Unoesc Videira, 2017)
The objective of this research was to observe the catalysis of soybean oil for the formation of the biodiesel. The catalyst studied was patassium iodide/mesoporous silica. The reaction occurred between soybean oil and methanol. The variables adressed during the reaction were temperature, residence time and catalysis on conversion to methyl ester. The variation of the parameters was efficient, however among the studied variables the best result was the temperature 20°C, with reaction time of 8 hours, 15% WT of iodide as well as 5% of catalyst base in weight of oil. The maximum conversion obteined under the described conditions was 90,09%. The only problem adressed was the high viscosity of the final product.